LINKAGE BETWEEN EURO FUTURES AND SPOT MARKET: EMPIRICAL EVIDENCE FROM INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Expanding trade between India and European  Union countries leads to increased EUR/INR  transactions which make the currency market  more volatile and riskier to trade. Traders and  investors who are exposed to currency fluctuations  try to hedge their risks by investing in euro  futures contracts. In this study, we assess EUR INR spot and futures prices from January 2010  – December 2019 using Grangers causality,  Johansen’s cointegration, and VECM techniques.  Stationarity of employed dataset is confirmed  using ADF test. Existence of long run equilibrium  between euro-rupee futures and spot market and  at least one cointegrating vector is confirmed  using Johansen’s cointegration. The Granger  causality results signify one-way causality betwixt  the price series where, futures prices lead spot  prices. The ECT is considered to be significant.  Thus, we conclude that the euro futures market  at National Stock Exchange (NSE) is efficient  and performs price discovery function. Traders,  retail investors, policy makers and mutual fund  managers who diversify their investments can  advance from this study.
Keywords: Euro Futures; Error Correction; Cointegration; Causality; Currency Derivatives